2009
DOI: 10.1177/0272431609332935
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and Victimization Among Native and Immigrant Adolescents in Norway

Abstract: This study compares levels of bullying others, victimization, and aggressiveness in native Norwegian and immigrant adolescents living in Norway and shows how bullying is related to proactive and reactive aggressiveness. The sample consists of 2,938 native Norwegians (1,521 girls, 1,417 boys) and 189 immigrant adolescents (97 girls, 92 boys) in school grades 8, 9, and 10. Data were collected via self-assessments. Structural equation models were conducted separately for girls and boys in both groups. The levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
90
1
20

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(120 citation statements)
references
References 43 publications
9
90
1
20
Order By: Relevance
“…Several studies have shown associations between lower socioeconomic status and involvement in bullying (see Tippett & Wolke, 2014, for a meta-analysis). With regard to migration background and exposure to bullying, findings from earlier studies are inconsistent (e.g., Fandrem, Strohmeier, & Roland, 2009;Hjern et al, 2013;Peguero, 2008;Wolke et al, 2001).…”
Section: Individual-level Characteristics Associated With Exposure Tomentioning
confidence: 96%
“…Several studies have shown associations between lower socioeconomic status and involvement in bullying (see Tippett & Wolke, 2014, for a meta-analysis). With regard to migration background and exposure to bullying, findings from earlier studies are inconsistent (e.g., Fandrem, Strohmeier, & Roland, 2009;Hjern et al, 2013;Peguero, 2008;Wolke et al, 2001).…”
Section: Individual-level Characteristics Associated With Exposure Tomentioning
confidence: 96%
“…(Seals y Young, 2003) o Canadá (McKenney, Pepler, Craig, y Connolly, 2006). Por otra parte, muchos estudios realizados en Europa no muestran diferencias significativas entre los grupos étnico-culturales en cuanto a la victimización (Durkin et al, 2012;Fandrem, Strohmeier, y Roland, 2009;Monks, Ortega-Ruiz, y Rodríguez-Hidalgo, 2008;Strohmeier, Kärnä, y Salmivalli, 2011). Algunos trabajos, menos numerosos, sí han encontrado dichas diferencias significativas" (Wolke, Woods, Stanford, y Schulz, 2001) y también a la hora de actuar como el agresor victimizado (Strohmeier, Spiel, y Gradinger, 2008).…”
Section: Introductionunclassified
“…Sin embargo, entre los diez tipos de victimización personal estudiados en la presente investigación, sólo dos fueron diferentes entre los grupos. Estos resultados están de acuerdo con otros estudios europeos recientes (Fandrem et al, 2009;Monks et al, 2008) y también con algunas investigaciones de los EE.UU. (McKenney et al, 2006;Seals y Young, 2003).…”
unclassified
“…Researchers in the past decades also concentrated on the role of ethnicity in bullying and victimization (e.g., Fandrem et al, 2009;McKenney et al, 2006;Vitoroulis and Vaillancourt, 2014), but this association has received little attention in the Hungarian context. Majority and minority students might have different likelihoods to be bullies or victims, and this association might be moderated by the ethnic composition of the class (Tolsma et al, 2013;Vervoort et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Prejudice might be expressed in the form of aggressive behavior towards minority students. Ethnic bullying is a special form of harassment and describes cases when students are bullied based on their ethnicity (Fandrem et al, 2009;Monks, Ortega-Ruiz and Rodríguez-Hidalgo, 2008;Verkuyten and Thijs, 2002).…”
Section: Introductionmentioning
confidence: 99%